1994
DOI: 10.1111/j.1399-3038.1994.tb00225.x
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil cationic protein in nasopharyngeal secretions and serum of infants infected with respiratory syncytial virus

Abstract: Eosinophil cationic protein (ECP) was assayed in nasopharyngeal secretion (NPS) and serum from 42 infants, hospitalized with acute lower respiratory infection, in El Salvador and the results analyzed in relation to etiology of the infection. ECP concentrations were high in NPS, at an average 50 times higher than those found in serum. Exceedingly high levels of ECP (> 1000 micrograms/L) were found more frequently in wheezing than in non-wheezing children (30% vs 7%) and, accordingly, were more commonly found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
28
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 22 publications
5
28
2
Order By: Relevance
“…The present results conflict with these studies, since ECP concentrations were similar in the two groups. The results of the present study are consistent with those reported by others [6,7]. In the latter study, no statistical difference in ECP/albumin ratio was found between 34 RSV+ and 27 RSV-infants with respiratory tract infection.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The present results conflict with these studies, since ECP concentrations were similar in the two groups. The results of the present study are consistent with those reported by others [6,7]. In the latter study, no statistical difference in ECP/albumin ratio was found between 34 RSV+ and 27 RSV-infants with respiratory tract infection.…”
Section: Discussionsupporting
confidence: 83%
“…In the latter study, no statistical difference in ECP/albumin ratio was found between 34 RSV+ and 27 RSV-infants with respiratory tract infection. However, we did not observe a difference in the ECP level of pharyngeal secretions between males and females, as described for the group of patients from El Salvador [7].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…However, one study, to support our findings of increased s-ECP levels in children with a history of wheeze, demonstrated increasing levels of s-ECP during the reconvalescent period after acute bronchiolitis in infants [25]. They also found higher s-ECP levels in infants with acute bronchiolitis than infants without a history of wheeze.…”
Section: Discussionsupporting
confidence: 62%
“…Other studies in older subjects have demonstrated increased s-ECP in asthmatic patients compared to those without asthma [12,13,23,24]. Several studies have demonstrated higher s-ECP levels in atopic compared to nonatopic subjects [13,25]. The presence or absence of atopy is not yet known in our subjects due to their young age.…”
Section: Discussionmentioning
confidence: 41%